The Effect of Twin Date Events and Ease of Use Access on Purchase Decisions (Case Study on Shopee E-Commerce in Tangerang) - Lailatul Uyun; Anggi Irawan; Sulfarid Sulfarid (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to test and analyze the effect of twin date events and ease of access to use on purchasing decisions in Shopee e-commerce. The sampling strategy in this study used purposive sampling. The participants in this study were residents of Tangerang City who used the Shopee application and made purchases at least twice a month. In determining the number of samples, researchers used the Lemeshow formula by getting 96 respondents. The data analysis method uses multiple linear regression with the data analysis tool in this study, namely, Statistical Product and Service Solutions (SPSS), and the type of research used is Quantitative. After the data was analyzed, this study found that the twin date event variable had a significant and positive effect on purchasing decisions and ease of use access also had a positive and significant effect on purchasing decisions in Shopee e-commerce. And with the results of the simultaneous coefficient of determination (R2) of 0.940, which means that 94% of purchasing decisions in Shopee e-commerce are influenced by twin date events and ease of access to use, while the remaining 6% is influenced by other variables not included in this study.